The Dynamics of Grief in Late Adolescence After Maternal Death in Terms of The Theory of Kübler-Ross - Dyana Putry Christanti Fitryani; Noorce Ch. Berek; Dian Lestari Anakaka; Indra Y Kiling (Journal of Health and Behavioral Science, 2021)
Adolescence is a developmental phase between childhood and adulthood. There are many experiences that teenagers get from the surrounding environment. These experiences are in the form of positive experiences or negative experiences that teenagers will receive in different ways. Individuals have different reactions to death events, including adolescents. The event of death can affect the development process, this is because death causes deep sorrow for adolescents. This study aims to examine the dynamics of late adolescent grief after maternal death in terms of the Kübler-Ross theory. According to Kübler-Ross, there are five stages that individuals have when experiencing grief, including denial, anger, bargaining, depression, and acceptance. Teenagers who experience maternal death will go through the five stages of grief from the Kübler-Ross. The results obtained are that some participants have not yet reached the acceptance stage because they still need time to accept the grief event that occurred. The discussion is expected to provide knowledge regarding the dynamics of late adolescent grief after maternal death in terms of the Kübler-Ross theory.